Association between influenza vaccination and cardiovascular outcomes in high-risk patients: A meta-analysis - Udell J.A. (2014)
IMPORTANCE: Among nontraditional cardiovascular risk factors, recent influenzalike infection is associated with fatal and nonfatal atherothrombotic events. OBJECTIVES: To determine if influenza vaccination is associated with prevention of cardiovascular events. DATA SOURCES AND STUDY SELECTION: A systematic review and meta-analysis of MEDLINE (1946-August 2013), EMBASE (1947-August 2013), and the Cochrane Library Central Register of Controlled Trials (inception-August 2013) for randomized clinical trials (RCTs) comparing influenza vaccine vs placebo or control in patients at high risk of cardiovascular disease, reporting cardiovascular outcomes either as efficacy or safety events. DATA EXTRACTION AND SYNTHESIS: Two investigators extracted data independently on trial design, baseline characteristics, outcomes, and safety events from published manuscripts and unpublished supplemental data. High-quality studies were considered those that described an appropriate method of randomization, allocation concealment, blinding, and completeness of follow-up. MAIN OUTCOMES AND MEASURES: Random-effects Mantel-Haenszel risk ratios (RRs) and 95% CIs were derived for composite cardiovascular events, cardiovascular mortality, all-cause mortality, and individual cardiovascular events. Analyses were stratified by subgroups of patients with and without a history of acute coronary syndrome (ACS) within 1 year of randomization. RESULTS: Five published and 1 unpublished randomized clinical trials of 6735 patients (mean age, 67 years; 51.3%women; 36.2%with a cardiac history; mean follow-up time, 7.9 months) were included. Influenza vaccine was associated with a lower risk of composite cardiovascular events (2.9% vs 4.7%; RR, 0.64 [95%CI, 0.48-0.86], P = .003) in published trials. A treatment interaction was detected between patients with (RR, 0.45 [95%CI, 0.32-0.63]) and without (RR, 0.94 [95%CI, 0.55-1.61]) recent ACS (P for interaction = .02). Results were similar with the addition of unpublished data. CONCLUSIONS AND RELEVANCE: In ameta-analysis of RCTs, the use of influenza vaccine was associated with a lower risk of major adverse cardiovascular events. The greatest treatment effect was seen among the highest-risk patients with more active coronary disease. A large, adequately powered, multicenter trial is warranted to address these findings and assess individual cardiovascular end points.